Genetic diversity of Amylostereum areolatum, the fungal symbiont of the invasive woodwasp Sirex noctilio in South Africa. Issue 6 (11th June 2018) - Mlonyeni, X. Osmond; Wingfield, Michael J.; Greeff, Jaco M.; Wingfield, Brenda D.; Slippers, Bernard
Abstract: Amylostereum areolatum is a wood‐decaying homobasidiomycete fungal symbiont of Sirex noctilio . Together, they cause serious damage to pine plantations in the Southern Hemisphere. The fungus reproduces asexually and is vertically transmitted by S. noctilio females, which results in extensive spread of clones. Specific A. areolatum clones are often dominant in areas invaded by the wasp. This is in contrast with the high diversity and complex invasion pattern of S. noctilio in most of these regions. In South Africa, for example, nuclear and mitochondrial ribosomal loci and vegetative compatibility group (VCG) markers on a small number of isolates have shown that only one genotype is present in the country. The aim of this study was to develop microsatellite markers for A. areolatum and determine the genetic diversity and structure of a relatively large collection of isolates of the fungus in South Africa. From five sequenced A. areolatum genomes, a total of 233 microsatellite primer pairs were designed, of which 57 were polymorphic among the genomes. Eleven of these polymorphic markers were then used in a population genetics study including 55 South African isolates. In a surprising manner, nine multilocus genotypes were found among these isolates, and with no population structure among different regions across South Africa. The single VCG previously identified for isolates from the country clearly do not correspond to a clone. The detected A. areolatum variation has relevance for the biology of the Sirex‐Amylostereum symbiosis, its introduction history into South Africa and its management through biocontrol. The microsatellite primers and data emerging from them also provide powerful tools for the study of A. areolatum populations in other parts of the world.